The integration Ki Hadjar Dewantara’s taxonomy into Barrett‘s criticism model - Iwan Zahar (2011)
Ki Hadjar Dewantara is the Founding Father of Indonesia National Education with his well known statements tringa, which are ngerti (cognitive domain), ngerasani (affective domain), and ngelakoni (psychomotor domain). The statements were given twenty years before Blomm’s Taxonomy (cognitive, affective and psychomotor) (Miarso, 2004). Other Dewantara’s famous statements are: niteni (to identify), niroake (to copy), and nambai (to modify or to add) which can be correlated with Bloom’s Taxonomy. The research started on September – December 2009 at Visual Communication Design, Tarumanagara University. The subjects of the research were fifty students in fifth semester. The fifth semester students were chosen to learn appreciation photos because the students have prior knowledge in appreciation arts. Survey research methods (Cresswell, 2008) were the main forms of inquiry used in this qualitative study. The survey research was designed to investigate hierarchy of leaning and to find questioning strategies which develop analytical skills and rasa (feeling-affective aspect). Student used Barrett‘s photo criticism model to interpret five images were projected through projectors along with the questions. The three questions were listed with each photographic images were (a) What do you see? (b) What does this photograph mean? And (c) How do you know? These three questions were similar to Barrett’s interpretation questions to students. Of the Barrett‘s Criticism Model and Ki Hadjar Dewantara’s Taxonomy, student level thinking and learning steps in photo appreciation can be grouped into three common categories. Level one, student can identify subject matter, denotation, medium, and form. Level two, student can apply principal design, element photographs, and connotation of photographs (rasa- affective aspect). Level three, student can compare and contrast photographs to identify the styles of photographer. I recommended questioning strategies to formulate art criticism questions within the hierarchical categories of Ki Hadjar Dewantara’s Taxonomy.